The relationship between perceived father and mother parenting styles and student academic achievement at SMK Methodist (ACS) Melaka / Noorhafizah Rubaai - Rubaai, Noorhafizah (2010)
This study is a correlational study as it was aimed at investigating the relationship between the perceived father and mother parenting styles (permissive, authoritarian, authoritative) with student academic achievement (based on PMR results) at SMK Methodist (ACS) Melaka. The sample used consisted of 47 form 4 students who were all males. The data was collected using 4 sets of questionnaires: the Demographic Information, Self-report Academic Achievement, Parental Authority Questionnaire Pertaining to Father, and Parental Authority Questionnaire Pertaining to Mother. The data was calculated using SPSS and Pearson-product Moment Correlation Coefficient (Pearson r). The findings showed that the majority of the students perceived their father and mother as authoritative. However, there was no relationship between father parenting styles with student academic achievement. On the other hand, mother parenting styles had been proven to be correlated with student academic achievement. This shows that mother parenting styles have an effect towards the students’ achievement. The results from this study are hoped to help parents to choose the best parenting style and get involve with their children’s development. It is recommended that future research to choose larger samples which are drawn from various schools in order to generalize the results.